Meningkatkan keputusan pembelian di Kopi Kenangan SPBU Pertamina (Sawangan Baru Depok) melalui sosial media co-creation - Aurellia, Reire; Silitonga, Parlagutan (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2023)
One of the business opportunities engaged in Food and Beverage that is much loved by all people is coffee. Franchise business in Coffee drink has been largely practiced in Indonesia. One of the famous franchisors is Kopi Kenangan. Coffee has become the beverage of choice for many people to start the day or accompany daily activities. This research aims to improve purchasing decisions with product quality and price perception through the role of social media mediation co-creation in Kopi Kenangan. The study population is coffee buyers during January 2023. The sample technique used to determine 150 respondents by Accidental Sampling. Existing respondent data were obtained from the collection of questionnaires. The analysis used is using PLS-SEM using Smart-PLS 3.0 software. The results showed almost all good and there was a significant influence between each variable, only for product quality variables on purchasing decisions alone there was no significant influence. It can be concluded that the relationship between product quality and purchasing decisions is not strong enough so that there is no positive and significant influence.